Clinical Impact and Predictors of Diffusion Weighted Imaging Reversal in Stroke Patients with Diffusion Weighted Imaging Alberta Stroke Program Early CT Score 0-5 Treated by Thrombectomy - Panni, Pietro; Lapergue, Bertrand; Maïer, Benjamin; Finitsis, Stephanos; Clarençon, Frédéric; Richard, Sébastien; Marnat, Gaultier (Clinical neuroradiology (Munich), 2022)
Purpose To determine whether reversal of DWI lesions (DWIr) on the DWI-ASPECTS (diffusion weighted imaging Alberta Stroke Program CT Score) template should serve as a predictor of 90-day clinical outcome in acute ischemic stroke (AIS) patients with pretreatment diffusion-weighted imaging (DWI)-ASPECTS 0-5 treated with thrombectomy, and to determine its predictors in current practice. Methods We analyzed data of all consecutive patients included in the prospective multicenter national Endovascular Treatment in Ischemic Stroke Registry between 1 January 2015 and 31 December 2020 with a premorbid mRS [less than or equal to]â¯2, who presented with a pretreatment DWI-ASPECTS 0-5 score, underwent thrombectomy and had an available 24â¯h post-interventional MRI follow-up. Multivariable analyses were performed to evaluate the clinical impact of DWIr on early neurological improvement (ENI), 3âmonth modified Rankin scale (mRS) score distribution (shift analysis) and to define independent predictors of DWIr. Results Early neurological improvement was detected in 82/211 (41.7%) of patients while 3âmonth functional independence was achieved by 75 (35.5%) patients. The DWI reversal (39/211, 18.9%) resulted an independent predictor of both ENI (aOR 3.6, 95% CI 1.2-7.7; p 0.018) and 3âmonth clinical outcome (aOR for mRS shift: 2.2, 95% CI 1-4.6; p 0.030). Only successful recanalization (mTICI 2c-3) independently predicted DWIr in the studied population (aOR 3.3, 95% CI 1.3-7.9; p 0.009). Conclusion The DWI reversal occurs in a non-negligible proportion of DWI-ASPECTS 0-5 patients subjected to thrombectomy and significantly influences clinical outcome. The mTICI 2c-3 recanalization emerged as an independent DWIr predictor.